If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28x + -91 = -35 Reorder the terms: -91 + 28x = -35 Solving -91 + 28x = -35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '91' to each side of the equation. -91 + 91 + 28x = -35 + 91 Combine like terms: -91 + 91 = 0 0 + 28x = -35 + 91 28x = -35 + 91 Combine like terms: -35 + 91 = 56 28x = 56 Divide each side by '28'. x = 2 Simplifying x = 2
| 8x-56=-72 | | 8x-56=72 | | -5x-6-2x=1 | | 3p=3p | | -2w-16=2w-8+8w+8 | | 4x=4x+(-12) | | -4x-32=144 | | 33+x=21 | | (2/3x-5)=(5/2x+3) | | 2/3x-5=5/2x+3 | | 5x-9x-x=35 | | 5x+6x-2x=18 | | -6x-y=-4y-2x | | 25X+14=75 | | 10x+9=20-x | | -2/3w-3/2=-5/7 | | 5x-29=x-5+4y | | -2/3w-3/2 | | 22+x=2y+30 | | .06/10.7= | | y=x^2+4x+-10 | | y=3x^2+14x+6 | | 5z^2+9z^2= | | 5x^2+5y^2-11xy-1=0 | | 2x-25+2x+40=180 | | 0.6/10.7 | | x-25+2x+40=180 | | 2y+10=7x | | x=21500+0.01x+0.25x | | 5x-10/12-6x | | 9x+11=13-1 | | Z=224 |